Biomasse - Daviron , Benoit (éditions Quae, 2019)
Based on abundant literature, Benoit Daviron sketches for us a long, economic and political history of the biomass. Farming is not just about providing food, nor is it alone in supplying the biomass. How, before and after the fossil energies, have European societies mastered the distance and mobilised the work to satisfy their growing needs? What consequences for the rest of the world? Over the years, we discover that the ability to mobilise energy and material, especially living beings, mirrors wealth and power in the leading country of the time. This book alters our queries about the future.